2005
DOI: 10.2134/jeq2003.0412
|View full text |Cite
|
Sign up to set email alerts
|

The Acetochlor Registration Partnership State Ground Water Monitoring Program

Abstract: The Acetochlor Registration Partnership (ARP) conducted a 7-yr ground water monitoring program at a total of 175 sites in seven states: Illinois, Indiana, Iowa, Kansas, Minnesota, Nebraska, and Wisconsin. While acetochlor [2-chloro-N-(ethoxymethyl)-N-(2-ethyl-6-methylphenyl)-acetamide] was the primary focus, the analytical methods also quantified alachlor [2-chloro-N-(2,6-diethylphenyl)-N-(methoxymethyl)-acetamide], atrazine [6-chloro-N-ethyl-N'-(1-methylethyl)-1,3,5-triazine-2,4-diamine], metolachlor [2-chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…The acetochlor OXA degradate was detected in ground water at only one site, Minnesota, at a maximum concentration of 1.4 μg L −1 (Table 6). These detection trends are entirely consistent with the pattern observed in the companion 175‐site acetochlor ground water monitoring program (De Guzman et al, 2005), in which acetochlor ESA was also detected more frequently than acetochlor OXA (24 vs. 6% of all samples analyzed had detections) and at higher concentrations (90th percentile annualized means were 0.87 to 1.28 μg L −1 for acetochlor ESA vs. <0.1 μg L −1 for acetochlor OXA).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The acetochlor OXA degradate was detected in ground water at only one site, Minnesota, at a maximum concentration of 1.4 μg L −1 (Table 6). These detection trends are entirely consistent with the pattern observed in the companion 175‐site acetochlor ground water monitoring program (De Guzman et al, 2005), in which acetochlor ESA was also detected more frequently than acetochlor OXA (24 vs. 6% of all samples analyzed had detections) and at higher concentrations (90th percentile annualized means were 0.87 to 1.28 μg L −1 for acetochlor ESA vs. <0.1 μg L −1 for acetochlor OXA).…”
Section: Discussionsupporting
confidence: 86%
“…This publication describes the methods, results, and interpretations of the acetochlor PGW monitoring program. The acetochlor ground and surface water monitoring programs are described in two companion publications (De Guzman et al, 2005; Hackett et al, 2005).…”
mentioning
confidence: 99%
“…Metolachlor has frequently been detected in groundwater, and concentrations have ranged from 0.08 to 4.5 µg L −1 in Wisconsin, Iowa and Pennsylvania from normal agricultural use 18, 19. A recent groundwater monitoring programme reported that metolachlor was rarely detected, but its ethanesulfonic acid (ESA) and oxanilic acid (OXA) metabolites were found at 106 and 63 sites tested respectively 20. This unexpected detection in groundwater indicates that more information is needed about the dissipation and eventual fate of metolachlor in subsoils as well as in surface soils.…”
Section: Introductionmentioning
confidence: 99%
“…For acetochlor, OXA is present at higher levels than ESA (mean pair‐wise difference in AMCs is 0.03 μg L −1 ). This trend is the opposite of what is seen for acetochlor degradates in shallow ground water, where acetochlor ESA is more frequently detected than acetochlor OXA and at higher concentrations (de Guzman et al, 2005). For both alachlor and metolachlor, ESA is more prevalent in surface water than OXA, by an average of 0.04 and 0.14 μg L −1 , respectively.…”
Section: Resultsmentioning
confidence: 71%